'n Ondersoek na die gebruik van musiek as 'n deel van die pastorale begeleiding van die adolessent - DuPlessis, Amanda Linda du (Verbum et ecclesia, 2014)
An investigation into the use of music as a part of pastoral counselling of the adolescent. Pastoral counselling of the adolescent could be a challenge, because adolescence is a period characterised by emotional fluctuation. During this period of the individual’s life, he or she begins to form his or her own identity and searches for a place in society, apart from the protection of their parents. Adolescents often do not have the necessary skills to deal with repressed emotions. Research shows that music has been used for many centuries in the healing process and that it has had a great influence on the psyche of human beings. For this reason, music can play an effective role in counselling adolescents. Music therapy involves the structural use of music and/or musical elements like rhythm, melody and harmony.